Recommended Essential Equipment for Basic Life Support and Advanced Life Support Ground Ambulances 2020: A Joint Position Statement. (20th April 2021) - Lyng, John; Adelgais, Kathleen; Alter, Rachael; Beal, Justin; Chung, Bruce; Gross, Toni; Minkler, Marc; Moore, Brian; Stebbins, Tim; Vance, Sam; Williams, Ken; Yee, Allen
Abstract: In continued support of establishing and maintaining a foundation for standards of care, our organizations remain committed to periodic review and revision of this position statement. This latest revision was created based on a structured review of the National Model EMS Clinical Guidelines Version 2.2 in order to identify the equipment items necessary to deliver the care defined by those guidelines. In addition, in order to ensure congruity with national definitions of provider scope of practice, the list is differentiated into BLS and ALS levels of service utilizing the National Scope of Practice-defined levels of Emergency Medical Responder (EMR) and Emergency Medical Technician (EMT) as BLS, and Advanced EMT (AEMT) and Paramedic as ALS. Equipment items listed within each category were cross-checked against recommended scopes of practice for each level in order to ensure they were appropriately dichotomized to BLS or ALS levels of care. Some items may be considered optional at the local level as determined by agency-defined scope of practice and applicable clinical guidelines. In addition to the items included in this position statement our organizations agree that all EMS service programs should carry equipment and supplies in quantities as determined by the medical director and appropriate to the agency's level of care and available certified EMS personnel and as established in the agency's approved protocols.